A case series on uterine anomalies and their obstetric outcomes - K. V., Swetha; Kala; Shanma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Congenital uterine anomalies (CUAs) are structural malformations of the female reproductive tract resulting from disruptions in the embryological development of the Müllerian ducts. These anomalies may remain undetected due to their asymptomatic nature but can significantly affect reproductive outcomes, including infertility, recurrent pregnancy loss, and complications during gestation and delivery. This case series presents five patients diagnosed with different types of uterine anomalies unicornuate, bicornuate, didelphys and septate uterus—each demonstrating distinct antenatal and postnatal trajectories. The series highlights the importance of accurate diagnosis, individualized management strategies, and multidisciplinary care to optimize maternal and neonatal outcomes.